Human chorionic gonadotropin and gonadotropin-releasing hormone influence pregnancy survival and resynchronized ovulation before timed artificial insemination in Holstein cattle - Buttrey, Brad Sterling (Kansas State University, 2008)
A study was performed to determine the minimum effective dose of human chorionic gonadotropin (hCG) needed to induce ovulation of follicles in cattle (Exp. 1). Another study determined the effects of replacing the first injection of GnRH (d -7) with hCG or saline in a Resynch-Ovsynch protocol [injection of GnRH 7 d before and 48 h after PGF[subscript2alpha] before a resynchronized fixed-timed AI (TAI)] on pregnancy rates in cows diagnosed not pregnant and pregnancy survival in cows diagnosed pregnant (d 0; Exp. 2). A final study determined the ovulation potential of hCG compared with GnRH and saline (Exp. 3). In Exp. 1, ovaries of Holstein cows were mapped by using transrectal ultrasonography 7 d before pregnancy diagnosis. Cows were assigned to treatments of saline, 100 [Mu]g of GnRH, or 500, 1,000, 2,000, or 3,000 IU of hCG. Ovarian structures were monitored 7 d later and proportion of cows and follicles that ovulated were recorded. In Exp. 2, cows in 4 herds were assigned to treatments of 1,000 IU of hCG, 100 [Mu]g of GnRH, or left as untreated controls 7 d before pregnancy diagnosis. Nonpregnant cows were given PGF[subscript2alpha] (d 0), then inseminated 72 h later, concurrent with a GnRH injection. Pregnancy rates tended (P = 0.08) to be increased by GnRH (17.9%; n = 703) compared with control (12.9%; n = 505), but not hCG (16.5%; n = 541). Incidences of ovulation in nonpregnant cows (Exp. 3) were: hCG (51.6%; n = 126), GnRH (46.1%; n = 102), and control (28.1%; n = 96), whereas those in pregnant cows were: hCG (59.3%; n = 59), GnRH (24.5%; n = 49), and control (6.9%; n = 58). We concluded that: 1) a minimum dose of 1,000 IU of hCG resulted in a greater ovulatory response than saline, GnRH, or 500 IU of hCG (Exp. 1); 2) initiating a Resynch-Ovsynch protocol 7 d before pregnancy diagnosis with saline reduced timed AI pregnancy rates (Exp. 2); and 3) incidence of new CL was greater after hCG than GnRH in pregnant cows, but not in nonpregnant cows (Exp. 3).
Keywords: hCG; GnRH; Ovulation synchronization; Estrus synchronization; Agriculture, Animal Culture and Nutrition (0475); Agriculture, General (0473)